Data-driven catalyst design for electrochemical CO2 reduction reaction (CO2RR) ... - Talebi, Pooya (Graduate Studies, 2023)
Carbon dioxide (CO2) poses significant global problems, primarily driving climate change and environmental degradation. Fossil fuel combustion leads to rising temperatures, extreme weather events, and ocean acidification. Addressing this challenge necessitates international cooperation, transitioning to renewable energy sources, and implementing policies to reduce emissions and the CO2content in the atmosphere. Electrochemical CO2 reduction (CO2RR) is a promising strategy to mitigate CO2 emissions and combat climate change. By utilizing renewable energy sources, such as solar or wind, CO2RR employs electrocatalysts to convert carbon dioxide into valuable chemicals and fuels. This technology aims to reduce CO2 levels in the atmosphere and to develop a sustainable and circular carbon economy, offering a potential pathway to tackle the challenges posed by excess carbon dioxide and promoting a greener, more efficient future. Nevertheless, numerous technical challenges must be addressed for successful CO2RR ...